The great state of white and high : Buddhism and state formation in eleventh-century Xia - Dunnell, Ruth W., 1950- (University of Hawai'i Press, 1996)
In the late tenth and eleventh centuries, a group of people known in Western and Japanese scholarship as the Tangut established an independent regime in the Ordos (present-day Ningxia, Shaanxi, Gansu, and Inner Mongolia). It quickly grew into the Xia empire, a multiethnic, multilingual state whose ruling dynasty, a people ethnically and linguistically related to Tibetans, adapted elements of Chinese and Inner Asian statecraft, culture, and religion.